Distribution of natural resources and population density in the merapi volcano area - Sutikno Sutikno; Widiyanto Widiyanto; Langgeng Wahyu Santosa; Andri Kurniawan; Taufik Hery Purwanto (Indonesian Journal of Geography, 2003)
The objective of this research is to study spatial distribution of natural resources and their relation to population density of the Merapi volcano area Survey method was used in this research, and started by thematic map and remote sensing imagery imerpretationdieldwork was carried out to check the interpretation result and to observe the actual natural resources in the sample areas were determined by purposive sampling. Population density data were collected by secondary data from sub-district. Descriptive, qualitative approach was used to data analysis and landform unit was used for evaluation of the natural resources.. The findings of this research are: spatially the natural resources, potency varies according to landform unit, and each landform unit has specific natural resources potency, it). the availability of the natural resources in the landform unit has closed relationship to the population density, high and enormous of natural resources usually followed by densely populated, the high densely populated area not always influenced by the existing of the natural resources but also by the functional of the area.